The Condition of Legal Stability in State's Contracts (A Preventive Means to Avoid Investment Disputes ) - جامع , شادي; كفروني , علي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The state declares its economic and investment policy through adopting a special law. The condition of legal stability arises to reflect quite apparently the safe and stable investment environment in the host state. However, as a natural outcome to the inequality of the investment contract parties (a sovereign state and a special person with no independent sovereignty), disputes could appear in the stage following concluding the contract, that may quite often be attributed to the effective dominance of state sovereignty over its territory. Here, the condition of legal stability plays a significant role in guaranteeing that the state performs no legal adjustment that could cause commitments or negatively affect the rights of the foreign investor as the second contracting party.